Polyester nasal swabs collected in a dry tube are a robust and inexpensive, minimal self-collection kit for SARS-CoV-2 testing. - Leah R Padgett; Lauren A Kennington; Charlotte L Ahls; Delini K Samarasinghe; Yuan-Po Tu; Michelle L Wallander; Shawna D Cooper; James S Elliott; Douglas Rains (PLoS ONE)
Background In order to identify an inexpensive yet highly stable SARS-CoV-2 collection device as an alternative to foam swabs stored in transport media, both contrived ("surrogate") CoV-positive and patient-collected spun polyester swabs stored in dry tubes were evaluated for time- and temperature-stability using qPCR. Methods Surrogate specimens were prepared by combining multiple, residual SARS-CoV-2-positive clinical specimens and diluting to near-LOD levels in either porcine or human mucus ("matrix"), inoculating foam or polyester nasal swabs, and sealing in dry tubes. Swabs were then subjected to one of three temperature excursions: (1) 4°C for up to 72 hours; (2) 40°C for 12 hours, followed by 32°C for up to 60 hours; or (3) multiple freeze-thaw cycles (-20°C). The stability of extracted SARS-CoV-2 RNA for each condition was evaluated by qPCR. Separate usability studies for the dry polyester swab-based HealthPulse@home COVID-19 Specimen Collection Kit were later conducted in both adult and pediatric populations. Results Polyester swabs stored dry demonstrated equivalent performance to foam swabs for detection of low and moderate SARS-CoV-2 viral loads. Mimicking warm- and cold- climate shipment, surrogate specimens were stable following either 72 hours of a high-temperature excursion or two freeze-thaw cycles. In addition, usability studies comprised of self-collected patient specimens yielded sufficient material for molecular testing, as demonstrated by RNase P detection. Conclusions Polyester nasal swabs stored in dry collection tubes offer a robust and inexpensive self-collection method for SARS-CoV-2 viral load testing, as viral RNA remains stable under conditions required for home collection and shipment to the laboratory.